Science - Kind, Vanessa; Taber, Keith (Teaching School Subjects 11-19, 2005)
In recognizing that new teachers often feel disempowered by the subject expertise they bring into teaching, this book not only covers the training standards for NQTs and the Induction Standards, but takes the reader beyond this by fully exploring issues relating to subject knowledge in learning to teach. Divided into three sections the book covers: framing the subject - defining subject knowledge and focusing on questions about science as a school subject teaching the subject - looking at pedagogical, curricular and pupil knowledge science within the professional community - focusing on the place of science within the wider curriculum and the teaching community. This refreshing new book provides stimulating assistance to subject specialists, from new teachers of science in the early years of professional development to those on a PGCE course or in their induction year. It is also suitable for subject leaders with mentor responsibilities and Advanced Skills Teachers undertaking specialist inset and teaching support.